Reduced Costs, Complications, and Length of Stay After Arthroscopic Versus Open Irrigation and Débridement for Knee Septic Arthritis. Issue 23 (1st December 2022) - Upfill-Brown, Alexander; Shi, Brendan; Carter, Matthew; Maturana, Carlos; Brodke, Dane; Shah, Akash A.; Hsiue, Peter; Photopoulos, Christos; Lee, Christopher; Stavrakis, Alexandra
Abstract : Background: In the treatment of native knee bacterial septic arthritis, the optimal irrigation and débridement modality—arthroscopic versus open—is a matter of controversy. We aim to compare revision-free survival, complications, and resource utilization between these approaches. Methods: The National Readmission Database was queried from 2016 to 2019 to identify patients using International Classification of Diseases, 10th revision, diagnostic and procedure codes. Days to revision irrigation and débridement (I&D), if any, were calculated for patients during index admission or subsequent readmissions. Multivariate regression was used for healthcare utilization analysis. Survival analysis was done using Kaplan-Meier analysis and Cox proportional hazard regression. Results: A total of 14, 365 patients with native knee septic arthritis undergoing I&D were identified, 8, 063 arthroscopic (56.1%) and 6, 302 open (43.9%). The mean follow-up was 148 days (interquartile range 53 to 259). A total of 2, 156 patients (15.0%) underwent revision I&D. On multivariate analysis, arthroscopic I&D was associated with a reduction in hospital costs of 5, 674 and length of stay of 1.46 days ( P < 0.001 for both). Arthroscopic I&D was associated with lower overall complications (odds ratio [OR] 0.63, P < 0.001), need for blood transfusion (OR 0.58, P < 0.001), and wound complications (OR 0.32, P < 0.001). Revision-free survival after index I&D was 95.3% at 3 days, 91.0% at 10 days, 88.3% at 30 days, 86.0% at 90 days, and 84.5% at 180 days. No statistically significant difference was observed between surgical approaches on Cox modeling. Discussion: Risk of revision I&D did not differ between arthroscopic and open I&D; however, arthroscopy was associated with decreased costs, length of stay, and complications. Additional study is necessary to confirm these findings and characterize which patients require an open I&D. Level of Evidence: III